What is preventing teachers from attaining assessment literacy? - Daniel, E.G.S. (Elsevier, 2012)
Many researchers have raised concerns that the lack of a correct basic definition of assessment would constrain research on assessment. Event more worrying is that teachers may not have any appropriate working theory to anchor their practices, instagating them to use ad hoc assessment practices. This is distinct especially as the act of assessing, at anytime, is normally a complex and multidimensional process. As such, it is believed that many teachers may be unable to cope with this demanding task, as result it is likely that students are prevented from acquiring skills such as problem-solving and creative thinking which are much needed skills for them to meet the challenges of the future. However, this situation may be amended if teachers were more assessment litarate. this article explains assessment litearcy and suggests ways of reducing the gap in assessment literacy among teachers.